Empowering Poor Women through Entrepreneurship Development towards a Creative Economy (Case Study of Duck Farming, Sumber Rejeki, Lamongan Regency) - Firdausi, M. Anwar; Sa'diyah, Halimatus; Rosyidah, Inayatur (Budapest International Research and Critics University, 2022)
From the economic aspect, women have an unfavorable position. Women are considered powerless because they are considered one eye. Poverty and women are things that are difficult to separate because poverty is often depicted with women's faces. So, it is necessary to optimize the development of entrepreneurship towards a creative economy that starts with efforts to optimize creativity based on women's empowerment so that they can increase economic independence. This research belongs to the type of descriptive qualitative research and field research, namely Sumber Rejeki Duck Farm, Tawangrejo Village, Turi District, Lamongan Regency. Data were collected through observation, interviews and focus group discussions in stages. Determination of sources of information (informants) in this study is purposive sampling with the snowball method. then the data were analyzed using the interactive analysis technique of Milles and Huberman . The results of this study are the empowerment of poor women is carried out through (1) guidance from the Lamongan Regency government in the form of the Lamongan Rural-Based Rural-Based People's Economic Movement Program (Gerlap). (2) the existence of the Sumber Rejeki Women Livestock Cooperative as a new economic institution in Tawangrejo Village and training from the relevant livestock service regarding natural resources supporting the fulfillment of duck feed and marketing networks.